The effects of camelina sativa oil and high-intensity interval training on liver function and metabolic outcomes in male type 2 diabetic rats - Kavyani, Zeynab; Dehghan, Parvin; Khani, Mostafa; Khalafi, Mousa; Rosenkranz, Sara K. (Frontiers in Nutrition, 2023)
The purpose of this study was to evaluate the independent and combined effects of camelina sativa oil and high-intensity interval training (HIIT) on liver function, and metabolic outcomes in streptozotocin-induced diabetic rats. Forty male Wistar rats were randomly assigned to five equal groups (8 per group): Normal control (NC), diabetic control (DC), diabetic + camelina sativa oil (300 mg/kg by oral gavage per day) (D + CSO), diabetic + HIIT (running on a treadmill 5 days/week for 8 weeks) (D + HIIT), diabetic + camelina sativa oil + HIIT (D + CSO + HIIT). TNF-α, MDA, PPAR -γ, and PGC-1α decreased in all three intervention groups (D + CSO, D + HIIT, and D + CSO + HIIT) compared to the NC (P<0.001), although the effects of D + CSO and D + CSO + HIIT were greater than D + HIIT alone. Hepatic TG decreased significantly in D + HIIT and D + CSO + HIIT compared to other groups (P<0.001). Fasting glucose in all three intervention groups (D + CSO, D + HIIT, and D + CSO + HIIT) and HOMA-IR in D + CSO with and without HIIT was decreased compared to DC (P<0.001). Whereas, D + CSO+ HIIT had the largest effect on fasting glucose and HOMA-IR. At the doses and treatment duration used in the current study, both CSO and HIIT were beneficial for reducing inflammation and oxidative stress, but HIIT seemed to be superior to CSO for reducing liver triglyceride content.